To the Question on Urine Diversion in Congenital Hydronephrosis in Children - D.V. Shevchuk; P.I. Voloshyn (Zaslavsky O.Yu., 2016)
Introduction. Hydronephrosis in children is an obstruction of pyeloureteral segment, which is usually diagnosed antenatal by ultrasound screening in 1.5 % of pregnancies. Pathophysiology is still unknown. The most common pathogenetic reasonable treatment of congenital obstruction pelvicoureteral segment (hydronephrosis) in children is a surgical treatment. As a rule, open methods are applied (by Hynes-Anderson and other methods). Recently endoscopic treatment has being discussed. Increasingly there are reports of the use of robotic equipment. According to the data of different authors successful results of Hynes - Anderson techniques reach 95 %. The question on the upper urinary tract drainage is still discussed. The choice of stent placement usually depends on the surgeon, although the analysis of literature data indicates a decrease in percentage of complications after stent using. The aim of the study. To analyze the methods and ways of urinary diversion in the surgical treatment of congenital hydronephrosis in children. Materials and methods. On the basis of the surgical department № 2 Zhytomyr Regional Children's Hospital (ZhRCH) for the period from 2000 to 2015 108 children were operated. The average age of patients was 3.8 years old. There were 38 (35.2 %) boys and 70 girls (64.8 %). The gold standard is Hynes - Anderson technique. Until 2006, external drainage of urinary tract surgery was mainly performed, while from 2006 close way was implemented, and from 2009 - the use of JJ-stent. Since 2010, videoassistant metnod was introduced (laparoscopic stage - mobilization of pelvicoureteral segment with further anastomosis through minilaparotomy access). In 2016 at the ZhRCH laparoscopic plastic was firstly performed for a boy aged 6 years old. The average duration of the intervention was 106 ± 32 min. Conclusions. The question on urinary tract drainage after pelvicoureteral segment plastic in children with congenital hydronephrosis should be considered individually only. The question on stent installation method remains unclear. After the indications for surgical treatment of congenital hydronephrosis in children are determined the function of the lower urinary tract must be considered to ensure the efficient derivation of urine in the postoperative period (the presence of concomitant neuromuscular dysfunction of the bladder).